The Juridical Nature of the Right to Favorable Environment: Principle vs Norm of Law - A. K. Bakhilina (Теоретическая и прикладная юриспруденция)
The article aims to test the author’s hypothesis that the right to favorable environment by its legal nature is rather closer to a principle than to a legal norm. The theoretical basis of the distinction between principle and norm of law is considered, special attention is paid to the study of the theory of the American lawyer and philosopher Ronald Dworkin. Relying on the concept of Dworkin, the author by the method of analogy provides arguments in support of his hypothesis. The confirmation of the proposed idea is also found in the decisions of international courts. Serious analysis of the legal framework, doctrinal sources and judicial practice was conducted in the course of writing the article.